Delivering good service: personal resources, job satisfaction and nurses' 'customer' (patient) orientation. (17th November 2013) - Gountas, Sandra; Gountas, John; Soutar, Geoffrey; Mavondo, Felix
Abstract Aims To explore the complex relationships between nurses' personal resources, job satisfaction and 'customer' (patient) orientation. Background Previous research has shown that nursing is highly intensive, emotionally charged work, which affects nurses' job performance and their customer orientation as well as patient or 'customer' satisfaction. This study contributes to the literature by examining how nurses' personal resources relate to their personal satisfaction and customer orientation and the relationships between them. Specifically, this study explores the effects of two facets of emotional labour (deep acting and surface acting), empathic concern, self‐efficacy and emotional exhaustion on personal job satisfaction and customer orientation. We also test the moderating effects of inauthenticity and emotional contagion. Design A quantitative survey. Method Data were collected through a self‐completion questionnaire administered to a sample of 159 Australian nurses, in a public teaching hospital, in 2010. The data were analysed using Partial Least Square analysis. Results Partial Least Square analysis indicates that the final model is a good fit to the data (Goodness of Fit = 0·51). Deep acting and surface acting have different effects (positive and negative) on job satisfaction and 'customer' orientation, self‐efficacy has a positive effect on both and emotional exhaustion has a positive effect on customer orientation and a negative effect on job satisfaction. The moderating effects of emotional contagion and empathic concern, in the final model, are discussed. Conclusions Understanding the complex interactions between personal resources, job satisfaction and customer orientation helps to increase service providers' (nurses in this study) personal satisfaction and 'customer' orientation particularly in difficult contexts.